Meningkatkan Motivasi dan Hasil Belajar Peserta Didik dengan Metode Demonstrasi pada Kelas III SDN 16 Mataram Tahun Ajaran 2022-2023 - Indrayadi Indrayadi; Siti Istiningsih; Deni Triagus Mahardika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
Motivation is what is most important in learning activities, so teachers must be able to cultivate students' learning motivation so that students in the classroom can achieve the learning goals set by the teacher. The problem that arises is the lack of motivation to learn, which leads to poor learning outcomes among students. Thus, learning is accompanied by demonstrations of making windmills and flat figures with folded symmetry to enhance students' learning motivation. The purpose of this study is to enhance the motivation and learning outcomes of SDN 16 Mataram Grade 3 students through demonstration method. This classroom action study involved 34 students and was conducted in two cycles, with each cycle consisting of planning, implementation, evaluation and reflection. The results of the study showed that student motivation and learning outcomes increased from Cycle 1 to Cycle 2 and reached completion of training.